Rapid Detection of the Marek's Disease Viral Genome in Chicken Feathers by Loop-Mediated Isothermal Amplification - Angamuthu, Raja (American Society for Microbiology, 2012)
A loop-mediated isothermal amplification (LAMP) method for the rapid detection of serotype 1 Marek's disease virus (MDV) was developed. The method used a set of three pairs of primers to amplify the MEQ gene for detecting serotype 1 MDV. The MDV LAMP method did not cross-react with serotype 2 and serotype 3, nor did the LAMP primers have binding sites for the common avian DNA viruses (reticuloendotheliosis virus, chicken anemia virus, subgroup J of the avian leukosis virus). Additionally, the assay could detect up to 10 copies of the MEQ gene in the MD viral genome, and it had 10 times higher sensitivity than the traditional PCR methods. The LAMP master mix was stable for 90 days at −20°C. Furthermore, the efficiency of LAMP for detection of serotype 1 MDV in clinical samples was comparable to those of PCR and viral isolation. The LAMP procedure is simple and does not rely on any special equipment. The detection of serotype 1 MDV by LAMP will be useful for detecting and controlling oncogenic Marek's disease.